The explicit closure for the ultrarelativistic limit of Extended Thermodynamics of Rarefied Polyatomic Gas - Pennisi, Sebastiano; Ruggeri, Tommaso (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In a recent paper the ultra-relativistic limit of a recent theory proposed by Pennisi and Ruggeri for polyatomic relativistic gas has been considered. This was important to check the general article. In particular, the explicitly expression of the characteristic velocities of the hyperbolic system were found for every value of the parameter a measuring ”how much” the gas is polyatomic. This result was achieved in terms of the components of the main field as independent variables and without writing it in terms of the physical variables. Here the closure of the field equations is considered in terms of these physical variables and their ultrarelatistic limit is obtained.